2014
DOI: 10.1109/jmems.2014.2360124
|View full text |Cite
|
Sign up to set email alerts
|

Multicamera Laparoscopic Imaging With Tunable Focusing Capability

Abstract: This paper presents a solution to overcome many of the fundamental challenges faced by current laparoscopic imaging systems. Our system is developed upon the key idea that widely spread multiple tunable microcameras can cover a large range of vantage points and field of view (FoV) for intraabdominal visualization. Our design features multiple tunable-focus microcameras integrated with a surgical port to provide panoramic intraabdominal visualization with enhanced depth perception. Our system can be optically t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Camera arrays have extensive applications in surveillance [ 1 ], robotics [ 2 ], Virtual Reality [ 3 , 4 , 5 ], surgery [ 6 ], and more. Multiple cameras placed on proper locations and poses may offer a wider field of view (FOV) by aggregating (stitching) individual images into a coherent, extended mosaic beyond what a single camera can provide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Camera arrays have extensive applications in surveillance [ 1 ], robotics [ 2 ], Virtual Reality [ 3 , 4 , 5 ], surgery [ 6 ], and more. Multiple cameras placed on proper locations and poses may offer a wider field of view (FOV) by aggregating (stitching) individual images into a coherent, extended mosaic beyond what a single camera can provide.…”
Section: Introductionmentioning
confidence: 99%
“…The camera placement problem is formulated in the context of building a camera array to enhance the vision quality of a laparoscopic surgery [ 6 ]. In current laparoscopic surgery, a single-camera with lighting is inserted through a trocar to provide desired view for surgeons to carry out surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [20] demonstrated a 3D integral-imaging endoscopy with tunable DOF by using a single large-aperture focal-length-tunable liquid crystal (LC) lens. Kanhere et al [21] introduced a multi-camera system to capture different views and stitch them together for a wider view. The above-mentioned methods add complexity to the laparoscope.…”
Section: Introductionmentioning
confidence: 99%
“…The miniaturized cameras are easily deployed and retrieved using the mechanical system of the TCA. Such convenient deployment and retrieval of the miniature cameras offered by this trocar design is an advantage over our previous attempts to apply multiple cameras at laparoscopic ports [ 22 , 23 , 24 ]. The TCA can provide a larger FoV compared to a current laparoscopic imaging system that uses a single camera, with the use of multiple miniaturized cameras.…”
Section: Introductionmentioning
confidence: 99%